(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article presents the targets of synthetic reading and gives the answers to the question why synthetic reading is still a relevant object at the institutions of higher education in our days. The aim of this method was to support reading of special texts in foreign languages without a dictionary.